2005
DOI: 10.1016/j.jasms.2004.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Automatic gain control in mass spectrometry using a jet disrupter electrode in an electrodynamic ion funnel

Abstract: We report on the use of a jet disrupter electrode in an electrodynamic ion funnel as an electronic valve to regulate the intensity of the ion beam transmitted through the interface of a mass spectrometer in order to perform automatic gain control (AGC). The ion flux is determined by either directly detecting the ion current on the conductance limiting orifice of the ion funnel or using a short mass spectrometry acquisition. Based upon the ion flux intensity, the voltage of the jet disrupter is adjusted to alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…Although this method of adjusting the ion population resembles automatic gain control (AGC) [25,26], it has some significant differences from other experimental methods that are used to select ion number. For example, the shape of the ion cloud may be influenced by the hexapole accumulation [17,27,28], and so we have compared these two ways of altering ion population to ensure that the frequency dependence is the same.…”
Section: Resultsmentioning
confidence: 99%
“…Although this method of adjusting the ion population resembles automatic gain control (AGC) [25,26], it has some significant differences from other experimental methods that are used to select ion number. For example, the shape of the ion cloud may be influenced by the hexapole accumulation [17,27,28], and so we have compared these two ways of altering ion population to ensure that the frequency dependence is the same.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of high mass accuracy by FTICR-MS can be found in the literatures [26,28,44,51,54], but these are often obtained using experimental conditions that are not optimal for high abundance dynamic range or high sensitivity. To advance the application of FT-ICR mass spectrometry for high-throughput proteomics, it is important to define procedures that achieve high mass accuracy on a routine basis.…”
Section: Discussionmentioning
confidence: 99%
“…However, Smith and coworkers demonstrated that mass accuracy using AGC depends strongly on the selected abundance level of the ion population. The mass accuracy obtained with a high ion population in the analyzer cell is not as good as for a low population [44,51]. The mass confidence levels using AGC reported by the Gygi and Smith groups are ϳ5 ppm for external calibration experiments [18,46,51].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…For example, a disk electrode "jet disrupter" was placed in the entrance region of the ion funnel to disperse the gas jet exiting the heated inlet capillary, thereby reducing the gas load to the following stage and prohibiting neutrals from entering the mass spectrometer [12]. The jet disrupter has also been used as an "ion valve" to regulate the intensity of the ion beam for use with automated gain control to improve mass measurement accuracy [13]. In addition, a controllable m/z filter was created at the exit of the ion funnel that removes lower mass chemical background species in some applications, and reducing down-stream space charge effects in ion trapping devices [14].…”
mentioning
confidence: 99%